2020
DOI: 10.1016/j.pmedr.2020.101227
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence and sociodemographic and geographic patterns of current menthol cigarette use among U.S. adults, 2005–2015

Abstract: Despite overall reductions in U.S. smoking prevalence, prior evidence suggests similar reductions may not have occurred for menthol cigarette users. This study examines nationally representative current menthol and non-menthol cigarette use prevalence and trends for adults (18+) overall and by sociodemographic and geographic characteristics using the 2005 (n = 31,132), 2010 (n = 26,967), and 2015 (n = 33,541) National Health Interview Survey. Between 2005 and 2015, non-menthol cigarette use decreased overall (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
6
15
0
Order By: Relevance
“…Despite the small sample size, the present study provides novel data, as few studies have reported any data on smoking, and menthol smoking in particular, social deprivation, nicotine dependence, and quitting behaviors among rural Black/African American women who face many social structural barriers to smoking cessation. These data are not generalizable, but our results are similar to what other studies have found among Black/African American women [14,17,[51][52][53]. It is also plausible that our data may reflect what future studies could find among Black/African American women smokers who live in similar rural, low-resource counties in the South.…”
Section: Strengths and Limitationssupporting
confidence: 75%
See 3 more Smart Citations
“…Despite the small sample size, the present study provides novel data, as few studies have reported any data on smoking, and menthol smoking in particular, social deprivation, nicotine dependence, and quitting behaviors among rural Black/African American women who face many social structural barriers to smoking cessation. These data are not generalizable, but our results are similar to what other studies have found among Black/African American women [14,17,[51][52][53]. It is also plausible that our data may reflect what future studies could find among Black/African American women smokers who live in similar rural, low-resource counties in the South.…”
Section: Strengths and Limitationssupporting
confidence: 75%
“…Prior studies have found that menthol smoking and flavored LCC use is most prevalent among African Americans, those with less education, and those living in poverty [51][52][53]. Mattingly and colleagues found that from 2005-2015, menthol cigarette smoking remained stable among those aged 25-34, with less than a high school education, with a household income less than $35,000, and those residing in the South, but it decreased among females and non-Hispanic Blacks [17]. Despite these trends, the prevalence of menthol cigarette smoking was highest among smokers with these sociodemographic characteristics [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…enthol cigarettes have been associated with increased youth experimentation and initiation and with decreased adult quitting success, 1−5 and the prevalence of menthol smoking has remained nearly constant in the U.S. over the past few decades. 6,7 Menthol cigarettes are disproportionately used by youth and young adults, women, non-Hispanic Blacks (NHBs), and other minorities. 4,6,8−12 Menthol is the only flavor currently allowed in cigarettes in the U.S.…”
mentioning
confidence: 99%